Neutrophil and Eosinophil DNA Extracellular Trap Formation: Lessons From Pathogenic Fungi - Silva, Juliana da Costa; Thompson-Souza, Glaucia de Azevedo; Barroso, Marina Valente; Neves, Josiane Sabbadini; Figueiredo, Rodrigo Tinoco (Frontiers in Microbiology, 2021)
Fungal infections represent a worldwide health problem. Fungal pathogens are responsible for a variety of conditions including since superficial diseases and allergic processes until potentially lethal invasive infections. Neutrophils and eosinophils have been implicated as effector cells in several pathologies. Neutrophils are major effector cells involved in the control of fungal infections and exhibit a plethora of antifungal mechanisms, such as phagocytosis, reactive oxygen species production, degranulation, and release of DNA extracellular traps (ETs). Eosinophils are polymorphonuclear cells classically implicated as effector cells in the pathogenesis of allergic diseases and helminthic infections, although their roles in both innate and adaptive immunity as immunomodulatory players are currently recognized. They are also endowed with antifungal activities and are abundantly found in allergic conditions associated with fungal colonization and sensitization. Neutrophils and eosinophils have been demonstrated to release their nuclear and mitochondrial DNA in response to many pathogens and proinflammatory stimuli. ETs have been implicated in the killing and control of many pathogens, but also as promoters and enhancers of inflammation and tissue damage. Formation of ETs by neutrophils and eosinophils has been described in response to pathogenic fungi. Here, we provide an overview of the mechanisms involved in the release of neutrophil and eosinophil ETs in response to different stimuli with a focus in fungal pathogens. General implications for the comprehension of the formation of ETs as well as their roles in the fungal infections are discussed here.